Ionometallurgical Step-Electrodeposition of Zinc and Lead and its Application in a Cycling-Stable High-Voltage Zinc-Graphite Battery - Chen, Peng; Richter, Janine; Wang, Gang; Li, Dongqi; Pietsch, Tobias; Ruck, Michael (Small, 2021)
Ionometallurgy is a new development aiming at the sustainable low-temperature conversion of naturally occurring metal ores and minerals to their metals or valuable chemicals in ionic liquids (ILs) or deep eutectic solvents. The IL betainium bis((trifluoromethyl)sulfonyl)imide, [Hbet][NTf2], is especially suited for this process due to its redox-stability and specific-functionalization. The potentiostatic electrodeposition of zinc and lead starting directly from ZnO and PbO, which dissolve in [Hbet][NTf2] in high concentrations is reported. The initial reduction potentials of zinc(II) and lead(II) are about −1.5 and −1.0 V, respectively. The ionic conductivity of the solution of ZnO in [Hbet][NTf2] is measured and the effect of various temperatures and potentials on the morphology of the deposited material is explored. The IL proves to be stable under the chosen conditions. From IL-solutions, where ZnO, PbO, and MgO have been dissolved, metallic Zn and Pb are deposited under potentiostatic control either consecutively by step-electrodeposition or together in a co-electrodeposition. Using the method, Zn is also deposited on 3D copper foam and assembles into high-voltage zinc-graphite battery. It exhibits a working-voltage up to 2.7 V, an output midpoint discharge-voltage of up to 2.16 V, up to 98.6% capacity-retention after 150 cycles, and good rate performance.
CRIS-Team Scopus Importer:2022-04-14
Keywords: high-voltage zinc-graphite batteries; ionometallurgy; step-electrodeposition; task-specific ionic liquids; zinc electrodeposition from ZnO